1999
DOI: 10.1095/biolreprod61.3.749
|View full text |Cite
|
Sign up to set email alerts
|

Role of Egg Sulfolipidimmobilizing Protein 1 on Mouse Sperm-Egg Plasma Membrane Binding1

Abstract: We have shown that sperm sulfolipidimmobilizing protein 1 (SLIP1, molecular mass of 68 kDa), a sulfogalactosylglycerolipid (SGG)-binding protein, is significant in sperm-zona pellucida (ZP) interaction. The objective of this study was to localize SLIP1 on the egg and determine its role in gamete interaction. Immunofluorescence and immunoprotein A gold electron microscopy localized SLIP1 to the egg plasma membrane. In vitro gamete binding, using zona-free eggs preincubated with antiSLIP1 Fab before coincubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In addition, SGG on the acrosome-reacted sperm head plays roles in sperm-egg plasma membrane interaction ( 44 ). SGG is also an integral component of sperm head…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SGG on the acrosome-reacted sperm head plays roles in sperm-egg plasma membrane interaction ( 44 ). SGG is also an integral component of sperm head…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it antiserum (IgG) generated against rat serum albumin (RSA), antiwas shown that a crude extract of SLIP1 can be prepared by RSA, were purchased from Organon Teknika Inc. (Scarborough, treating intact testicular cells or gametes (Law et al, 1988;ON, Canada). A goat anti-rabbit immunoglobulin conjugated with Tanphaichitr et al, 1993;Ahnonkitpanit et al, 1999) proteins from intact cells (Carter and Hakomori, 1977).…”
Section: Methodsmentioning
confidence: 99%
“…Previously described procedures were used to prepare IgG fraction Lingwood and his associates have further demonstrated that from anti-SLIP1 antiserum (Tanphaichitr et al, 1993), to formylate rat testis SLIP1 can be purified from its AES crude extract to anti-SLIP1 IgG to reduce non-specific binding to spermatozoa (Lingwood, 1985), to generate affinity-purified anti-SLIP1 IgG a single 68 kDa band on sodium dodecyl sulphate-polyacryl- (Ahnonkitpanit et al, 1999), and to conjugate a fluorochrome, Cy3…”
Section: Methodsmentioning
confidence: 99%
“…In mouse fertilization, the importance of the major glycolipid, sulfogalactosylglycerolipid (SGG) 1 on the sperm surface has been shown, because a SGG-recognizing protein, sulfolipid immobilizing protein 1 (SLIP1), is present on both egg and sperm surfaces (3,8). Egg SLIP1 is suggested to be involved in sperm-egg plasma membrane binding through its binding to SGG (9). Recently, a liposome containing SGG has been shown to bind the zona pellucida, the egg extracellular glycoprotein matrix, suggesting the presence of another binding counterpart to SGG in the zona components of the mouse (10).…”
mentioning
confidence: 99%